2011
DOI: 10.1159/000325730
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Enhancement of ex vivo Gene Therapy Neuroprotection in a Rodent Model of Retinal Degeneration

Abstract: Aims: We have previously shown the benefits of cell-based delivery of neuroprotection in a rodent model of retinitis pigmentosa (RP). In order to maximise the effectiveness of this approach, we hypothesised that this could be augmented by combination with an aminoglycoside known to limit the abnormal RNA translation seen in this model. Methods: A rhodopsin TgN S334ter-4 rat model of RP underwent daily subcutaneous injection of 12.5 µg/g gentamicin from postnatal day 5 (P5). At P21, selected rats also underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 90 publications
1
8
0
Order By: Relevance
“…56 We recently used a combinatorial approach of aminoglycoside read-through to treat the underlying genetic defect in the rat S334ter model coupled with glialderived neurotrophic factor neuroprotection, which fully rescued the retinal degeneration, whereas individually we found that these treatments had limited efficacy. 57 In this study, we have shown that RIP3-dependent necroptosis is the underlying molecular cause of cone cell death in the pde6c w59 model, whereas rod cells are dying via caspase-dependent apoptosis. Thus, development of effective treatment strategies for retinal degeneration affecting both rods and cones requires components that target both the primary genetic deficit and the secondary bystander cell loss.…”
Section: Discussionmentioning
confidence: 73%
“…56 We recently used a combinatorial approach of aminoglycoside read-through to treat the underlying genetic defect in the rat S334ter model coupled with glialderived neurotrophic factor neuroprotection, which fully rescued the retinal degeneration, whereas individually we found that these treatments had limited efficacy. 57 In this study, we have shown that RIP3-dependent necroptosis is the underlying molecular cause of cone cell death in the pde6c w59 model, whereas rod cells are dying via caspase-dependent apoptosis. Thus, development of effective treatment strategies for retinal degeneration affecting both rods and cones requires components that target both the primary genetic deficit and the secondary bystander cell loss.…”
Section: Discussionmentioning
confidence: 73%
“…This previously published data with gentamicin in conjunction with the present significant elevated read‐through efficiency of NB54 or PTC124 compared to that of gentamicin, suggests that these two TRIDs should induce the recovery of sufficient amounts of functional harmonin protein to combat or at least slow down the retinal degeneration in USH1 patients. Moreover a combined treatment of TRIDs with neurotropic factors may have an even higher capacity to treat nonsense mutation‐based retinal diseases as indicated by Gregory‐Evans et al (2011). Finally, in further investigations, the co‐administration of poly‐ L ‐aspartic acid (PAA), which has been shown to enhance aminoglycoside‐induced read‐through and decrease aminoglycoside‐induced toxicity, may provide an additional approach to enhance the efficacy of aminoglycoside variants NB30 and NB54 for the treatment of USH1 (Swan et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The concept of neuroprotection by inhibiting cell death has emerged over the last decade and a range of factors, such as ciliary neurotrophic factor (CNTF), brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF), and basic fibroblast growth factor (bFGF), have been identified as potential neuroprotectants. Major concerns with the neurotrophic factors are either they are too large to cross the blood-retinal barrier (BRB) or are associated with undesirable systemic complication [20]. Cell-based therapies, with their paracrine effects, have overcome the complexities associated with systemic delivery of these molecules.…”
Section: Eye Disordersmentioning
confidence: 99%